'I want to, but I also need to': start-ups resulting from opportunity and necessity - Marco Caliendo; Alexander S. Kritikos (Institute for the Study of Labor (IZA), 2009)
When unemployed persons go into business, they often are characterized as necessity entrepreneurs, because push factors, namely their unemployment, likely prompted their decision. In contrast to this, business founders who have been previously employed represent opportunity entrepreneurs because pull factors provide the rationale for their decision. However, a data set of nearly 1,900 business start-ups by unemployed persons reveals that both kind of motivation can be observed among these start-ups. Moreover, a new type of entrepreneur emerges, motivated by both push and pull variables simultaneously. An analysis of the development of the businesses reflecting three different motivational types indicates a strong relationship between motives, survival rates and entrepreneurial development. We find in particular that start-ups out of opportunity and necessity have higher survival rates than do start-ups out of necessity, even if both types face the same duration of previous unemployment.
Keywords: D81; J23; M13; 330; Entrepreneurship; push and pull motives; survival and failure; job creation; Unternehmer; Unternehmensgründung; Selbstständige; Arbeitslosigkeit; Unternehmensentwicklung; Beschäftigungseffekt; Deutschland